ANALISIS PENYEBAB TINGGI KEHAMILAN TIDAK DIINGINKAN DI PROVINSI KEPULAUAN BANGKA BELITUNG (NOURA: Jurnal Kajian Gender dan Anak, 2022)
Unwanted Pregnancy is a condition where a woman does not want her pregnancy. In contrast to women who want pregnancy, in the case of women with KTD it will result in various risks, including increasing the Maternal Mortality Rate (MMR) because with KTD cases a woman will be less concerned with her pregnancy which is at risk in the decision to continue the pregnancy without carry out treatment for pregnancy or intentionally abort the pregnancy which also has the potential to cause death to the mother. The KTD rate in the Bangka Belitung Islands Province based on the Program Performance and Accountability Survey (SKAP) for the Population, Family Planning and Family Development Program (KKBPK) in 2019 was 29.9 percent, this figure is much higher than the national percentage of 17.5 percent. This study was conducted to identify and analyze the factors that cause the high number of unwanted pregnancies in the Province of the Bangka Belitung Islands. This study uses BKKBN secondary data obtained by descriptive analysis, factor analysis and multinomial logistic regression analysis. The results of this study were that the pregnancy status in the Province of the Bangka Belitung Islands consisted of 66.67% of desired pregnancies, 23.08% of pending pregnancies (not on time) and 10.25% of unwanted pregnancies. Factors that significantly affect unwanted pregnancy are contraceptive use, knowledge of contraceptives, age, number of surviving children, and marital status. Unwanted Pregnancy tends to occur in women aged 20-30 years with 1-3 children still alive, has knowledge of contraception, has used contraception, is not working, has a junior-high school education level and lives in rural areas.